Implementasi Nilai-Nilai Pancasila dalam Literasi Digital pada Gen Z - Yvonne Chika Junata; Anastasia Rachel Tanuwidjaja; Margaretha Sabda Djaja; Devi Jong; Fransiska Indra Sulistyawati; Jap Tji Beng (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
The digital era has transformed how Gen Z interacts, learns, and engages in social life. This shift highlights the need to strengthen national values so that technology use remains aligned with the character and moral principles of Pancasila. This study aims to provide an in-depth understanding of the implementation of Pancasila values in relation to the digital literacy of Gen Z in Indonesia. Using a scoping review approach, it examines previous studies that discuss the connection between Pancasila education, digital literacy, and character development in the digital era. The findings show that Pancasila values play a positive role in shaping Generation Z’s digital ethics, critical thinking, and social responsibility in online spaces. The main challenges include the instant culture, the spread of hoaxes, and the decline in communication ethics. Therefore, integrating Pancasila-based digital character education within schools and universities is essential. Future research is encouraged to explore how other generations implement Pancasila values and to adopt more diverse methodological approaches to gain deeper insights into the relationship between Pancasila values and digital literacy.